ECONOMIC AND SOCIAL BENEFITS OF ROBOTICS IN SOLAR AND BIOMASS ENERGY: A REVIEW WITH IMPLICATIONS FOR BIHAR - Kumari, Mamta; Sinha, Pankaj Chandra; Sinha, Pallav Chandra; Hasnain, Md Gauhar; Sah, Vikash Kumar; Kumar, Dhananjay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Robotics integration in the renewable energy sectors of solar and biomass energy can change energy production, improve efficiency, and introduce sustainability practices. This review paper will address some of the economic and social benefits of robotics in such energy domains, specifically for the state of Bihar in India, where substantial challenges in the production of energy are present. To initiate, the paper will discuss the situation of solar and biomass energy in Bihar: where this state is still poor concerning the provision of electricity, which indicates the amount of dependency that the state has with the conventional energy, and thus how urgent the need is for alternative sustainable sources. We then analyze the appraisal of how robotics can maximize energy production through automation, precision agriculture, and predictive maintenance-cutting operational costs and therefore maximizing energy output. The paper discusses various robotic applications such as automated solar panel cleaning systems and biomass processing robots, about which emphasis was placed for improving productivity and operational efficiency. We also take into account the socio-economic impacts of introducing robotics into these energy sectors. Improved access to energy, through more efficient modes of production, holds the promise of lifting local economic performance and providing employment opportunities and reducing energy poverty. However, the paper also addresses some of the possible challenges, such as some displacement of jobs and hence the need for upgradation in skills in response to new technologies. To put this into perspective, the literature synthesis and case studies are reviewed below to give an overview of successful implementations of robotics in renewable energy globally. We further discuss policy recommendations and strategies that must be integrated into Bihar's energy framework to support sustainable development goals and address regional energy demands. Hence, in conclusion, the strategic deployment of robotics in solar and biomass energy does not merely serve to provide significant economic advantage but also contributes to social development of Bihar to ensure a viable and sustainable future of the energy world.